A gestão hídrica no perímetro irrigado Poções da Ribeira: uma abordagem através da Educação Ambiental - Souza, Diego Silva (2018)
Faced with the current water crisis, it is necessary to reassess the degree of conservation of water bodies, especially reservoirs (dams), in order to maximize their possibilities of use. In this sense, sensitizing the population becomes an essential prerogative for the promotion of water sustainability, and consequently, it is possible to ensure the consumption of future generations. Taking into account the standards set by the National Environment Council (CONAMA) for each use for which the water is intended, the levels of conservation of the reservoir water are elements of concern, mainly because they are water bodies of multiple uses . In this context, this research consisted in sensitizing the students of the Agribusiness Integrated Technical Course of the Federal Institute of Education, Science and Technology of Sergipe - Campus Itabaiana / SE, on the water management in the Potions of Ribeira (Itabaiana / SE) Irrigated Perimeter, aiming at thus conserving for multiple uses of this water body. With regard to methodological procedures, this research was classified at the exploratory level, having as a procedure a case study. Therefore, because it is the management of water resources, it is proposed to approach the environmental sciences, and for this it is necessary to use Environmental Education (EA) as a pillar, in order to promote reflection and foster social participation in the water management of Iridescent Perimeter Potions of Ribeira. Thus, it is based on the clarification of the student community about the conditions of degradation and conservation of the water body under study, so that these become disseminators of legal aspects associated with the management of water resources, especially that practiced on the spot by the managing body. Regarding the results, structured questionnaires applied with open and closed questions were used as a tool for collecting data. Finally, this research brings the production and implementation of a didactic resource, which according to the choice of the participating student sample, consisted of a game in quiz format, which will contribute substantially to the training of future agribusiness professionals, through the proposed discussion on management.